Corona virus and its effect to personal and community in the interest being entrepreneurs at Ponorogo, Indonesia / Shinta Maharani and Diana Sri Wulandari - Maharani, Shinta; Wulandari, Diana Sri (Universiti Teknologi MARA, Perlis, 2020)
Nowadays the outbreak of coronavirus (covid19) which increasingly takes souls to make Quarantine policy for each country is the most important thing. The quarantine and stay at home policy predicted would cause the loss of jobs, because of the work stoppage. The prohibition of government to get out of their home has been a pressing source of income of the primary in the economics sector. The huge raised alert status of the coronavirus from yellow to red. It indicates the spread of coronavirus is very serious and has a wide impact on public health, because of this disease, unemployed condition or unable to find work due to intense competition and selection in looking for jobs. Awareness to be able to have an entrepreneurial spirit, being an entrepreneur are increased and considered. Indonesian workers (15 years and above) prefer to work as officers, but now they change their mind, while junior and school graduates are the highest contributors to unemployment in Ponorogo, Indonesia. The purpose of this study: 1. To analyze the influence of coronavirus to personal factors on entrepreneurial interest in Ponorogo, Indonesia 2. To analyze the influence of coronavirus to community on entrepreneurial interests in Ponorogo, Indonesia 3. To analyze the influence of coronavirus on personal and community simultaneously on the interests of being entrepreneurs in Ponorogo Indonesia. The method in this study is a quantitative approach, with simple random sampling to 96 respondents. The data collection is a questionnaire. Data analysis used instrument test consisting of validity and reliability test, classic assumption test, hypothesis test consisting of multiple linear regression test, R square test, F test, and ttest. The results showed that the coronavirus effect partially has a positive and significant influence on personal factors and the community being entrepreneurial interest. Simultaneously personal factors and the community have a significant influence on the entrepreneurial interest amounted to 54, 7 %, while the rest influenced by other variables not examined in this study.